Effect of Strontium Metal Doping on Crystal Structure and Band Gap Energy of Zinc Oxide Nanoparticles - Heru Harsono; Mauludi A. Pamungkas; Ach. A. Dardiri; Febriane I. Kurnia; Cintya P. Anandari (Syntax Corporation Indonesia, 2024)
Nanotechnology is a basic science that discusses the relationship between size, dimensions, and physical properties of nanostructured materials. This study aims to determine the effect of strontium administration on the crystal structure of ZnO nanoparticles. In this study, zinc oxide (ZnO) was doped with strontium using the coprecipitation method. The basic ingredients used are zinc chloride, strontium chloride, HCl solution, and NaOH precipitating solution. Variations in the concentration used for strontium doping are 0%, 3%, 5%, and 7%. The characterization was carried out by testing with XRD to determine the crystal structure, and UV-Vis to determine the band gap in the ZnO material. The results of the XRD diffraction test showed that the crystal structure of the sample was wurzite and orthorhombic. The crystal size was calculated using the Scherrer equation, and the crystal sizes obtained varied, namely ZnO of 101.28 nm, 3% of 61.19 nm, 5% of 94.91 nm, and 7% of 82.73 nm. The results of the characterization of the energy gap measurements carried out using the Tauc Plot method show that the application of strontium doping to ZnO nanoparticles causes a decrease in the value of the energy gap.